Combining Efficiency and Stability in Mixed Tin–Lead Perovskite Solar Cells by Capping Grains with an Ultrathin 2D Layer. Issue 12 (7th February 2020) - Wei, Mingyang; Xiao, Ke; Walters, Grant; Lin, Renxing; Zhao, Yongbiao; Saidaminov, Makhsud I.; Todorović, Petar; Johnston, Andrew; Huang, Ziru; Chen, Haijie; Li, Aidong; Zhu, Jia; et al.
Abstract: The development of narrow‐bandgap ( E g ≈ 1.2 eV) mixed tin–lead (Sn–Pb) halide perovskites enables all‐perovskite tandem solar cells. Whereas pure‐lead halide perovskite solar cells (PSCs) have advanced simultaneously in efficiency and stability, achieving this crucial combination remains a challenge in Sn–Pb PSCs. Here, Sn–Pb perovskite grains are anchored with ultrathin layered perovskites to overcome the efficiency‐stability tradeoff. Defect passivation is achieved both on the perovskite film surface and at grain boundaries, an approach implemented by directly introducing phenethylammonium ligands in the antisolvent. This improves device operational stability and also avoids the excess formation of layered perovskites that would otherwise hinder charge transport. Sn–Pb PSCs with fill factors of 79% and a certified power conversion efficiency (PCE) of 18.95% are reported—among the highest for Sn–Pb PSCs. Using this approach, a 200‐fold enhancement in device operating lifetime is achieved relative to the nonpassivated Sn–Pb PSCs under full AM1.5G illumination, and a 200 h diurnal operating time without efficiency drop is achieved under filtered AM1.5G illumination. Abstract : Stable and efficient mixed tin–lead (Sn–Pb) perovskite solar cells (PSCs) are demonstrated by defect passivation with ultrathin layered perovskites. The passivation layer provides defect passivation both at the film surface and the grain boundaries, without blocking the carrier transport. The devices exhibit a certified power conversion efficiency (PCE) of 18.95%, and a 200 h diurnal operating stability.